Internalisasi Islamic Parenting dalam Meminimalisir Pergaulan Bebas pada Majelis Taklim Muslimah di kabupaten Sorong - Fitri Siyami; Sudirman; Fardan Abdillah M; Indria Nur; Andi Ahriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this research is to identify the free association that occurs among the children of female Muslim study group members in Sorong district, to analyze the internalization of Islamic parenting in the families of the female Muslim study group congregants att Sorong regency, and to assess the challenges and obstacles faced in internalizing Islamic parenting in the families of the female Muslim study group congregants at Sorong regency. This type of research is qualitative descriptive. The approach of this research is a phenomenological approach, and the data sources consist of primary data from interviews and secondary data from books and documentation. The data collection methods in the research use observation, interviews, and also documentation. The data processing and analysis techniques involve data reduction, data presentation, and drawing conclusions. The results of this study indicate that, firstly, the promiscuity that occurs is caused by several factors, namely a lack of parental attention, a lack of religious understanding, mistakes in choosing a social environment, and a tendency to use mobile phones and social media. Promiscuity consists of two types of deviant behavior, namely consuming alcoholic beverages and engaging in sex outside of marriage. Secondly; The internalization of Islamic parenting as expressed by twenty-six informants is relevant to the concept of Islamic parenting theory put forward by Al-Atas and Al-Ghazali regarding the introduction of beliefs and worship, the presence of role modeling, habituation, selection of formal and non-formal educational institutions, especially in religious education, providing a space for discussion, providing supervision and punishment as a means of shaping children's morals and interactions, as well as providing rewards to enhance children's motivation for worship. Thirdly; Factors that hinder and challenge the internalization of Islamic parenting include the limited resources of speakers or ustadz or those delivering sermons who are experts in the field of parenting, the different backgrounds of the congregation in the study group, the lack of supporting facilities, insufficient religious understanding and attention from parents, the mistake of choosing the environment, and the misuse of mobile phones and social media. The implications in this research are divided into theoretical implications, which strengthen the theory of Islamic parenting according to Al-Ghazali and Al-Attas, and the theory of religious socialization proposed by Ronald L. Johnston. Meanwhile, the practical implications are expected for the management of study groups and those delivering sermons to consistently enhance their role as a source of knowledge in non-formal educational institutions that are greatly needed by the community, to encourage the participants of the women's study groups to continually learn and reflect on themselves, and for teenagers and pre-adolescents to always be cautious and protect themselves from free association that can endanger themselves and those they care about.